El policía descalzo de la Plaza San Martín : el segundo caso del comisario Lascano - Mallo, Ernesto, 1948- (Nuevos tiempos (Madrid, Spain), 2011)
Superintendent Lascano is drawn into a war between the Buenos Aires Chief of Police and the Apostles, drug-dealing cops who want to control the city. When the Chief of Police is murdered Lascano becomes the Apostles' next target. His only way out of the country is to retrieve the loot from a bungled bank robbery. Mallo paints a scathing portrait of Argentina where the Junta's generals are paraded in court in civilian clothes, treated like mere petty thieves. The mothers and grandmothers of The Plaza de Mayo see the people who have stolen their children go unpunished; corruption and violence continue to rule. But at the centre of the novel is a touching portrayal of two broken men, a cop and a robber, whose humanity is sorely tested by the times and events racking this proud country.